PORTFOLIO ASSESSMENT TRENDS ON FUTURE LEARNING - Afriadi, Bambang (Jurnal Evaluasi Pendidikan, 2021)
This text discusses in-depth study and tests the assessment of the adaptive portfolio. Assessments will consistently diagnose problems and how educators perform solutions from less than optimal learning. The matching method is done by matching and comparing the characteristics of several similar studies with criteria so that one particular conclusion is obtained. Furthermore, a systematic review is used, a Narrative systematic review, to review relevant studies. This text is about anticipating a new version of the assessment program into the current learning reform efforts. Portfolio development is more challenging than they expected. Portfolios can gather the information that can be used to evaluate student achievement in the classroom